Analysis Of Patient Satisfaction On Online Registration System Compared To Onsite Registration Systemat Pandan Arang Boyolali Hospital - Nur'aini -; Trismianto Asmo Sutrisno; Astri Sri Wariyanti (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2023)
Background. Pandan Arang Boyolali Regional General Hospital is a type B referral hospital with an average of 250 patient visits per day. In 2019 the Pandan Arang Boyolali Hospital has implemented an online registration system called the BAPER application (booking check queue), which can be accessed from home by patients, this online registration system is intended to improve service quality in outpatient care, but the system still has many obstacles. Objective. Knowing the Patient Satisfaction of the Online Registration System Compared to the Onsite Registration System at Pandan Arang Boyolali Hospital. Method. The type of research used in this research is quantitative. The research design used is comparative. The population in the study were 1,034 outpatients who visited in Nopember 2022. Purposive sampling technique. chi square data analysis, Results. Description of patient satisfaction with the online registration system Most of them are satisfied as many as 24 respondents (52,2%) Description of patient satisfaction with the onsite registration system Most of them are quite satisfied as many as 23 respondents (50%) Conclusion. There is a difference in satisfaction between the online and onsite registration systems with a p value = 0.008.